ENTREPRENEURSHIP AND ETHICS NAVIGATING THE CHALLENGES OF ETHICAL BUSINESS PRACTICES IN STARTUPS - Endang Fatmawati; Mohammad Abdul Mukhyi; Agus Leonard Togatorop; Wilson Marpaung; Ahmad Muhajir (Branding: Jurnal Manajemen dan Bisnis, 2024)
In recent years, the entrepreneurial landscape has witnessed a surge in the establishment of startups. While these ventures bring innovation and economic growth, they also face significant ethical challenges. This study explores the complexities of maintaining ethical business practices within startups. Utilizing a normative legal research method, the research draws on various previous studies and statutory laws in Indonesia to analyze how ethical considerations are integrated into business operations. The findings reveal that while many startups strive to adhere to ethical standards, they often encounter dilemmas due to limited resources, competitive pressures, and the evolving regulatory environment. This paper aims to provide insights into the importance of ethical business practices and offers recommendations for startups to navigate these challenges effectively.